Thursday

April 17, 2014

April 17, 2014

Posted by **bob** on Monday, June 3, 2013 at 7:54pm.

- math -
**Reiny**, Monday, June 3, 2013 at 9:23pmt1 = 23 ---> a = 23

t3 = 92 --->ar^2 = 92

divide them

r^2 = 4

r = ± 2

sum(n) = a(r^n - 1)/(r-1) = 6813

If r = 2

23( 2^n - 1)/(2-1) = 6813

2^n - 1 = 296.21... ------> not a whole number

so there can't be a sum of 6813

if r = -2

23((-2)^n - 1)/(-2-1) = 6813

(-2)^n = -887.65...

no way!

This question either has a typo , or the question itself is flawed.

proof:

suppose we had 4 terms

sum(4) = 23(2^4 - 1)/1 = 345

sum(5) = 23(2^5 - 1)/1 = 713

...

sum(8) = 5865 ----

sum(9) = 11753

or

sequence is

23 + 46 + 92 + 184 + 368 + 736 + 1472 + 2944 + 5888 +

**Related Questions**

math - in a geometric series t1=23,t3=92 and the sum of all of the terms of the ...

math - in a geometric series t1=23,t3=92 and the sum of all of the terms of the ...

math - sorry for before it is my first time using this website and this is the ...

Math help quickly - Use the expressions for left and right sums and the table ...

Calculus need help badllyyy! - Use the expressions for left and right sums and ...

sum geometric series - what is the sum of geometric infinite series 3/2+ 9/16+ ...

CALC II - Determine the convergence of the following series using the nth-...

math studies - An arithmetic series has a first term of -4 and a common ...

Math - Geometric Series - Find the sum of the geometric series 128 - 64 + 32...

Algebra II (Geometric Series) - What is the sum of the following geometric ...